Richard Hooker and the Sufficiency of Scripture - LeTourneau, Mark S. (Journal of Anglican studies, 2016)
This article compares the doctrine of scripture in Richard Hooker's Lawes of Ecclesiasticall Politie with that of John Calvin's Christianae religionis institutio (Institutes of the Christian Religion) to assess Hooker's Reformed credentials in this domain. Hooker departs from Reformed orthodoxy in two ways: first, as is generally recognized, in denying the autopisticity of Scripture; second, though less widely recognized, in decoupling autopistis from the internal testimony of the Holy Spirit. These departures must be weighed against countervailing considerations: the unanimity between Hooker and Calvin on the substance of autopistis and the need for Church testimony in attesting to Scripture; their disparate audiences and exigencies, including, in Hooker's case, possible Puritan association of autopistis with scriptural omnicompetence; Hooker's reliance on Article 6 of the Articles of Religion in its entirety in defending scriptural sufficiency; and the silence of Hooker's contemporary critics regarding his denial of autopistis.